HUBUNGAN PAPARAN DEBU DENGAN GANGGUAN PERNAFASAN PADA PEKERJA PEMBUATAN BATU BATA DI JATI BARU KECAMATAN PAGAR MERBAU KABUPATEN DELI SERDANG TAHUN 2020 - Wilda Wahyuni Siregar; Supran Hidayat Sihotang; Raisha Octavariny; M. Wiradana Perangin-Angin (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2020)
Dust is the most frequent and dangerous chemical factor in the workplace. Based on the Republic of Indonesia Minister of Manpower Regulation No. 13 of 2011 concerning the Threshold Value (NAV) of Physical and Chemical Factors in the Workplace, the maximum dust content in the workplace is 3 mg / m3. Exposure to dust that exceeds the NAV can cause breathing problems in workers in the form of a decrease in forced expiratory volume in one second and a decrease in the volume of vital capacity. This research is a quantitative analytical survey with cross sectional design that aims to determine the relationship of dust exposure with respiratory problems in brick making workers. The population in this study were all combustion brickworkers, a total of 34 samples taken using total sampling techniques. Data were analyzed using Chi Square test with Î± = 0.05. The results showed that most brick making workers were exposed to dust exposure for> 8 hours (79.4%) and most of the workers had respiratory problems (76.5%). Based on statistical tests it is known that there is a relationship between dust exposure and respiratory problems in brick making workers in Jati Baru, Pagar Merbau District, Deli Serdang Regency in 2020 (p value = 0.004). Long exposure to the environment containing work dust particles will cause severe stress on the respiratory tract organs, making it easy to cause various types of lung disease and other respiratory diseases. Therefore, the owner of the brick making factory is expected to be able to provide personal protective equipment (PPE) such as masks for workers and provide sanctions if workers do not use PPE.